2018
DOI: 10.1152/ajprenal.00071.2018
|View full text |Cite
|
Sign up to set email alerts
|

Role of (pro)renin receptor in albumin overload-induced nephropathy in rats

Abstract: Proteinuria is not only a common feature of chronic kidney diseases (CKD) but also an independent risk factor promoting CKD progression to end-stage renal failure. However, the underlying molecular mechanisms for protein overload-induced renal injury remain elusive. The present study examined the role of (pro)renin receptor (PRR) in pathogenesis of albumin overload (AO)-induced nephropathy and activation of intrarenal renin-angiotensin system (RAS) in rats. Wistar rats underwent unilateral nephrectomy and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…However, this has not been demonstrated directly in kidney tubules of mice with ureteral obstruction due to the amount of tubular fluid necessary for AngII analysis. Alternatively, the increase of urinary AngII has been used as a marker of iRAS activation during CKD development in rats (Fang et al, 2018). In general, this iRAS activation results in hemodynamic changes with GFR reduction, observed as a plasma creatinine increase in UUO mice and in increases in the intraluminal pressure leading to tubular dilation observed in the proximal tubule ( Table 1 and Figure 2 , respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this has not been demonstrated directly in kidney tubules of mice with ureteral obstruction due to the amount of tubular fluid necessary for AngII analysis. Alternatively, the increase of urinary AngII has been used as a marker of iRAS activation during CKD development in rats (Fang et al, 2018). In general, this iRAS activation results in hemodynamic changes with GFR reduction, observed as a plasma creatinine increase in UUO mice and in increases in the intraluminal pressure leading to tubular dilation observed in the proximal tubule ( Table 1 and Figure 2 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that the anti-inflammatory and anti-fibrotic effects observed by aliskiren can be achieved alone or in combination with calcium channel blockers and valsartan (Wu et al, 2010). On the other hand, Fang and collaborators showed that the administration of PRO20, a decoy inhibitor of PRR, prevents renal increase of TGF-β1, oxidative stress, and interstitial fibrosis in rats with albumin overload (Fang et al, 2018). They demonstrated that PRR antagonism dramatically reduces the proteinuria, which has been recognized as an independent risk factor of CKD progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 15-25-nt and 30-40-nt RNA fractions were collected for high-throughput examination of RNA modification by LC-MS/MS (Supplemental Figure S1). 7,11 These analyses resulted in the identification and quantification of 16 types of RNA modifications.…”
Section: Altered Small Rna Modification Profiles In the Cerebral Cortmentioning
confidence: 99%
“…According to new findings, nearly all RAS components may have a big effect on the development of CKD and its predisposing factors, such as hypertension. The activity of the prorenin receptors (PRR), which is found in the collecting duct cells of the kidney and increases the affinity of renin for angiotensinogen, is significant for RAS activation [23]. PRR blockade in animal models causes the decrease of RAS activity, which indirectly decreases levels of proteinuria, macroscopic signs of interstitial fibrosis and renal fibrosis.…”
Section: Role In Kidney Failurementioning
confidence: 99%